2018
DOI: 10.1111/ppl.12809
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced tolerance to a combination of heat stress and drought in Arabidopsis plants deficient in ICS1 is associated with modulation of photosynthetic reaction center proteins

Abstract: Plants are exposed to multiple abiotic stresses that simultaneously occur under natural environmental conditions. Studies deciphering acclimation of plants to stress combinations are, however, still scarce. ISOCHORISMATE SYNTHASE 1 (ICS1) is known as a crucial enzyme required for synthesis of salicylic acid and phylloquinone, one of the components of the photosystem I complex. Although the significance of ICS1 in the regulation of abiotic stress response and pathogen defense in plants has been evidenced in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…ICS1 is involved in the biosynthesis of SA and phylloquinone. In a study, the Arabidopsis ICS1 mutant, sid2‐1 , exhibits heat and drought tolerance via H 2 O 2 ‐dependent stomatal closure and hyper‐accumulated total soluble sugars (Kumazaki & Suzuki, 2019). In a study, an SA‐BINDING PROTEIN 4 (SABP4) overexpression from Lycium chinense in tobacco confers drought tolerance by stimulating the SA level and ROS homeostasis enzymes (Li, Wang, et al, 2019).…”
Section: Phytohormones Action and Response Mechanism In Drought Stressmentioning
confidence: 99%
“…ICS1 is involved in the biosynthesis of SA and phylloquinone. In a study, the Arabidopsis ICS1 mutant, sid2‐1 , exhibits heat and drought tolerance via H 2 O 2 ‐dependent stomatal closure and hyper‐accumulated total soluble sugars (Kumazaki & Suzuki, 2019). In a study, an SA‐BINDING PROTEIN 4 (SABP4) overexpression from Lycium chinense in tobacco confers drought tolerance by stimulating the SA level and ROS homeostasis enzymes (Li, Wang, et al, 2019).…”
Section: Phytohormones Action and Response Mechanism In Drought Stressmentioning
confidence: 99%
“…The mutant analysis of SA biosynthesis or catalase-deficient mutants suggest that ROS can also function upstream of SA biosynthesis, suggesting that ROS and SA function in a self-amplifying feedback loop [23,54]. For example, by analyzing the mutants deficient in SA signaling (sid2), it was shown that the mutants accumulated higher ROS levels and showed tolerance to a combination of heat and drought stress [129,147]. Another study suggested that the exogenous application of SA increased the heat tolerance in tomatoes and barley by improving the antioxidant defense system through the scavenging of ROS [148,149].…”
Section: Hormone and Ros Crosstalk During High Temperatures Stressmentioning
confidence: 99%
“…In addition, a decline in SA accumulation was observed in Arabidopsis upon the combination of heat stress and drought [ 21 ], although SA accumulation increased in citruses in response to the same stress combination. A recent study demonstrated that Arabidopsis plants deficient in isochorismate synthase 1 (ICS1), named sid2-1 , showed higher tolerance to a combination of heat stress and drought [ 134 ]. ICS was shown to be required for SA synthesis, as well as for the production of phylloquinone, one of the components of the PSI complex that mediates the electron transfer from PSI to ferredoxin [ 135 ].…”
Section: Response Of Plant To Heat Stress Combined With Other Abiomentioning
confidence: 99%